The Moral Values found in EFL Textbook "When English Rings a Bell" - -, Dela Leka Andromeda; Nirwanto, Rahmadi; Qamariah, Zaitun (Indonesian Journal of Teaching and Learning, 2023)
This study aims to find out what moral values are represented in an EFL textbook for Indonesian Junior High School students: “When English Rings a Bell”. This study used a qualitative research. This study was be focused on the English textbook "When English Rings a Bell" produced by the Ministry of Education and Culture of Indonesia for eighth grade junior high school students. The data are collected using content analysis methods. The findings revealed the total frequencies from chapter one until chapter thirteen from the least to the most apparent in the English Textbook “When English Rings a Bell”. The result of the data also showed the most frequently moral values that appeared in this English textbook are Discipline (20%), Hard work (16%), Love to Read (9%). These three words the most apparent in the particular chapter of the English textbook and they related to the eighteen moral values in the table.